Early mobilization following elective ankle lateral collateral ligament reconstruction in adults. (May 2023) - Al-Janabi, Mina Mazin; Apostolides, Michael; Southgate, Crispin; Dhinsa, Baljinder Singh
Abstract: Background: Emergency departments in the UK are overwhelmed with musculoskeletal trauma, 50 % of which resulting from ligamentous injuries. Of these, ankle sprains are the most prevalent, however with poor rehabilitation in the recovery period, 20 % of patients may develop chronic instability that may necessitate operative reconstruction. At present, there are no national guidelines or protocols to help direct postoperative rehabilitation and determine weightbearing status. Our aim is to review the existing literature that investigated postoperative outcomes following different rehabilitation protocols in patients with Chronic Lateral Collateral Ligament (CLCL) instability. Methods: A literature search was performed via Medline, Embase and Pubmed databases using the terms 'ankle', 'lateral ligament', 'repair'. 'reconstruction' and 'early mobilisation'. A total of 19 studies were identified after filtering that they were English language papers. A gray literature search was also performed using the Google search engine. Results: Based on the literature reviewed, patients undergoing early mobilisation and Range Of Movement (ROM) following lateral ligament reconstruction for chronic instability seem to have better functional outcomes and earlier return to work and sports. This is however in the short-term, and there are no medium to long-term studies evaluating the effects of early mobilisation on ankle stability. Furthermore, there may be an increased risk of postoperative complications, mainly wound related, with early mobilization compared to delayed mobilization. Conclusion: Further randomized studies and long-term prospective studies with larger cohorts of patients are required to improve the level of evidence available but based on current literature it would appear that controlled early ROM and weight-bearing is advisable in patients undergoing surgery for CLCL instability. Highlights: 20 % of patients sustaining ankle sprains may develop chronic instability. Early mobilisation and ROM following LCL reconstruction for chronic instability may offer better functional outcomes and earlier return to work and sports. There may be increased risk of postoperative complications, mainly wound related, with early mobilization compared to delayed mobilization.